2016
DOI: 10.1007/s00253-016-7661-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel DeoR-family member from the Streptomyces ahygroscopicus strain CK-15 that acts as a repressor of morphological development

Abstract: Wuyiencin is produced by Streptomyces ahygroscopicus var. wuyiensis, which has been widely used in China as an industrially produced biopesticide to control various fungal diseases. Although its mechanism of action, breeding, and fermentation had been extensively characterized, less is known about the regulatory functions that affect its biosynthesis or morphological development. The wysR3 gene of S. ahygroscopicus strain CK-15, a novel member of the DeoR family of regulatory genes, was assessed to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The nucleoside antibiotic wuyiencin is one such secondary metabolite; it is produced by Streptomyces ahygroscopicus var. wuyiensis, which was first isolated from the natural soil habitat of Wuyi Mountain in China [10]. After being industrially produced (COFCC-R-0903-0070), wuyiencin has been extensively used to control various fungal diseases in vegetables and crops and to enhance their resistance to diverse pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleoside antibiotic wuyiencin is one such secondary metabolite; it is produced by Streptomyces ahygroscopicus var. wuyiensis, which was first isolated from the natural soil habitat of Wuyi Mountain in China [10]. After being industrially produced (COFCC-R-0903-0070), wuyiencin has been extensively used to control various fungal diseases in vegetables and crops and to enhance their resistance to diverse pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…We identified that the wysR3 gene was also a transcriptional regulator belonging to the DeoR family, which had any significant function in sugar metabolism or antibiotic production except morphological development (Liu et al 2015). In addition, we found that the DwysR3 mutant strain can grow quickly to reach a plateau stage of maximum biomass at 60 h, which is 12 h faster than the wild-type strain (Ge et al 2016). As a result, we conducted this present study to evaluate the effect of overexpression of wysR in a DwysR3 mutant strain, and we explore a new method to breeding the genetic engineering strain combined the characteristics of fast morphological development and high yield of wuyiencin.…”
Section: Introductionmentioning
confidence: 92%
“…Positive colonies containing wysR gene fragments showed a 663 bp insert and were further selected for DNA preparation and sequencing. The resulting pSTE-wysR construct was then transferred from E. coli ET12567 (pUZ8002) to the DwysR3 mutant strain (Ge et al 2016) by intergeneric conjugation. The integrative plasmid pSETC cannot replicate in Streptomyces; so stable exconjugants should be obtained only if pSETC has been integrated into the chromosome of the recipient strain.…”
Section: Construction Of Wysr Overexpression Strainmentioning
confidence: 99%
“…Pathway-specific transcriptional regulation, which is the most fundamental level, is mediated by regulatory genes encoded within the respective biosynthetic gene clusters ( Vicente et al, 2015 ). Some regulatory factors affect antibiotic production, while others affect morphological development and production of antibiotics via processes that are sometimes genetically coupled by shared transcriptional regulators ( Hur et al, 2008 ; Ge et al, 2016 ). A few regulatory factors are involved only in morphological development, an example being MtrA, which is crucial for normal development of aerial hyphae of the model strain S. coelicolor ( Cui et al, 2016 ; Zhang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…WysR3, a novel member of the DeoR family of regulators, had no effect on antibiotic production, but acted as a repressor during morphological development. The Δ wysR3 strain grew faster than the WT, reaching the plateau stage of maximum biomass 12 h earlier in the flasks ( Ge et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%